Interspecific variation in conspecific negative density dependence can make species less likely to coexist. (20th August 2018) - Stump, Simon Maccracken; Comita, Liza S.
Abstract: Conspecific negative density dependence (CNDD) is thought to promote plant species diversity. Theoretical studies showing the importance of CNDD often assumed that all species are equally susceptible to CNDD; however, recent empirical studies have shown species can differ greatly in their susceptibility to CNDD. Using a theoretical model, we show that interspecific variation in CNDD can dramatically alter its impact on diversity. First, if the most common species are the least regulated by CNDD, then the stabilising benefit of CNDD is reduced. Second, when seed dispersal is limited, seedlings that are susceptible to CNDD are at a competitive disadvantage. When parameterised with estimates of CNDD from a tropical tree community in Panama, our model suggests that the competitive inequalities caused by interspecific variation in CNDD may undermine many species' ability to persist. Thus, our model suggests that variable CNDD may make communities less stable, rather than more stable.